Respuesta :
R - 9S = 2 --------- (1)
3R - 3S = -10 -----(2)
(1)x 3
3R - 27S = 6 --------(1a)
(1a) - (2):
-3s - ( -27s) = -10 - 6
- 3s + 27s = -16
24s = -16
s = -2/3 ---- sub into (1)
R - 9(-2/3) = 2
R + 6 = 2
R = 2 - 6
R = -4
Ans: R = -4, S = -2/3 [Answer: (-4, -2/3) ]
3R - 3S = -10 -----(2)
(1)x 3
3R - 27S = 6 --------(1a)
(1a) - (2):
-3s - ( -27s) = -10 - 6
- 3s + 27s = -16
24s = -16
s = -2/3 ---- sub into (1)
R - 9(-2/3) = 2
R + 6 = 2
R = 2 - 6
R = -4
Ans: R = -4, S = -2/3 [Answer: (-4, -2/3) ]
the correct answer for R and S are
R = - 4
S = - 2/3
( -4, - 2/3)
R = - 4
S = - 2/3
( -4, - 2/3)